Fischfang in der Rhön (an der Sinn) - Bergman-Michel, Ella (Germany, 1932)
The film is contained with other pieces: Wo wohnen alte Leute / Where Old People Live 1931, (13 min.), Erwerbslose kochen für Erwerbslose / Unemployed are Cooking for the Unemployed 1932, (9 min.), Fliegende Händler in Frankfurt am Main / Travelling Hawkers in Frankfurt am Main1932, Work print (21 min.), Wahlkampf 1932 (Letzte Wahl) / Election Campaign 1932 (Last Election) 1932/33, (13 min.), music scores by Günter A. Buchwald, Fliegende Händler in Frankfurt am Main / Travelling Hawkers in Frankfurt am Main 1932, rough cut (46 min.), Fragmente / Fragments (1 min.), Mein Herz schlägt Blau - Ella Bergmann-Michel / Blue is the Beat of my Heart - Ella Bergmann-Michel Jutta Hercher & Maria Hemmleb, 1989, (30 min.).